The Effect of Self-Control and Peer Conformity on Pre-Marital Sexual Behavior Among Students at SMK “X” in Ciparay District - Annatasya Maesa Kurnia; Rifqi Farisan Akbar (Sean Institute, 2026)
Adolescence is a transitional period characterized by biological, psychological, and social changes that increase vulnerability to risky behavior, including premarital sexual behavior. This phenomenon is increasingly worrying among Indonesian adolescents and is also clearly found in students at SMK “X” in Ciparay District. This study aims to analyze the influence of self-control and peer conformity on premarital sexual behavior among students at SMK “X” in Ciparay District. The study used a quantitative approach with a survey method. The study sample consisted of 64 students in grades X and XI selected using proportional random sampling technique. Data were collected through a Likert scale questionnaire that measured premarital sexual behavior, self-control based on Averill's theory, and peer conformity based on Baron and Byrne's theory. Data analysis was performed using multiple linear regression with the help of IBM SPSS. The results showed that self-control had a significant and negative effect on premarital sexual behavior, while peer conformity had a significant and positive effect. Simultaneously, self-control and peer conformity had a significant effect on premarital sexual behavior and were able to explain 23.1% of the variation in that behavior. These findings suggest that low self-control and high levels of peer conformity that support risky behavior increase the likelihood of premarital sexual behavior in students. This research is expected to provide a basis for schools, parents, and other stakeholders in designing more effective preventive interventions.